Analysis of the multiplicity of equilibrium profiles in tubular reactor models*. Issue 18 (2016) - Dochain, D.
Abstract: This paper deals with the analysis of the non isothermal tubular reactor model. It is shown in particular and in line with similar studies on biochemical reactor models that multiple equilibrium profiles can be exhibited if the diffusion coefficients are large enough. The consequence on the stability of these equilibrium profiles is that these also exhibit the alternance of stable and unstable equilibrium profiles.